Analisis Dampak Sosial Ekonomi BUMDes MOZAIK di Desa Pematang Serai, Kabupaten Langkat - Handriyani Dwilita; Pipit Buana Sari; Yurika Aulia (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
BUMDes was established to be one of the solutions to the inequality between development in cities and development in villages. BUMDes are specifically regulated for their establishment and management based on laws and government regulations that aim to improve the welfare of village communities through the use of potential and resources in the village, both financial resources and natural and human resources. BUMDes MOZAIK is one of the BUMDes established in Pematang Serai village for the purpose of improving the welfare of the Pematang Serai village community. BUMDes MOZAIK has been established since 2016 and has experienced ups and downs in running BUMDes business units, until now there are only 3 business units left. In accordance with the purpose of the establishment, BUMDes is an element that supports village development, so that BUMDes should have a social and economic impact on the village. This research aims to analyze the social and economic impacts that BUMDes MOzaik has provided to the village community. This research uses descriptive qualitative analysis with data reduction analysis techniques. The research data was collected using the interview method to 9 research samples from the village apparatus, BUMDes MOZAIK managers and the community. The research variables were developed based on indicators of social impact and economic impact from various literature sources. The results revealed that BUMDes MOZAIK has had a social impact because of the social changes that have occurred in the community but it is still very small. Meanwhile, the economic impact has not clearly appeared because the existence of BUMDes MOZAIK is still economically felt by a handful of people, and the economic contribution of BUMDes to Village Original Revenue is also still small in value. This can also be seen from the absence of an increase in the income of the Pematang Serai Village community with the BUMDes.